Monitoring the impact of COVID-19 in Myanmar: Agricultural production and rural livelihoods in two irrigation schemes – October 2020 survey round - Lambrecht, Isabel B.; Ragasa, Catherine; Mahrt, Kristi; Aung, Zin Wai; Ei Win, Hnin; Zu, A Myint; Wang, Michael (International Food Policy Research Institute, 2020)
The persistent and worsening effects of the COVID-19 crisis on rural household incomes are alarming. The onset of the second wave of infections and mitigation measures in Myanmar is continuing to depress household incomes. Key findings: Almost three-quarters of the households surveyed reported lower household income than usual in August and September. In addition to a drought and lack of irrigation water limiting crop production in August and September, 22 percent of farmers experienced difficulties accessing inputs and 28 percent invested less than usual in their farm due to financial constraints. A quarter of farmers experienced difficulties selling their produce, which is lower than the share that reported having such difficulties in previous months. However, farmers anticipate further difficulties hampering sales in coming months, mainly due to expected restrictions on mobility. Landless households have been the most adversely affected by the crisis, largely due to lost nonfarm employment, lower remittances, and further negative impacts on rural enterprises. To cope with reduced incomes, 61 percent of households reported having reduced food expenditures, 36 percent sold assets, and 37 percent took loans. Households maintained the diversity of their diets but reduced the amount of meat and fish consumed. More households reported meat and fish to be less available than in previous rounds. Government transfer programs reached 99 percent of households in the study area, mostly in the form of income assistance. Recommended actions: Assistance to rural households should be continued to soften the impact of reduced income during the COVID-19 crisis and prevent households from jeopardizing future food security and health by depleting savings and assets, acquiring debt, and reducing food expenditures. Supporting rural non-farm businesses and employment will be key to building resilience in household livelihoods and to achieving a faster overall economic recovery.